MODEL PEMBERDAYAAN MASYARAKAT ISLAM KOTA PADANG MELALUI DANA CORPORATE SOSIAL RESPONSIBILITY (CSR) PT. SEMEN PADANG BERBASIS KEARIFAN LOKAL - Harvius Harvius; M. Bahri Ghazali; Hasan Mukmin; Fitri Yanti; Oriza Agustin; Muhamad Rudi Wijaya (Nizham Jurnal Studi Keislaman, 2019)
The purpose of this study is to find a model of empowering the Islamic City of Padang through the Corporate Social Responsibility Fund (CSR) of PT. Semen Padang based on local wisdom. The research method uses qualitative approach. The data source is the manager of empowerment through CSR funds of PT. Semen Padang and the community who received CSR funds from PT. Semen Padang. As the result, after applying the Islamic community empowerment model through the Corporate Social Responsibility Fund (CSR) of PT. Semen Padang, the people who were initially helpless become empowered, independent, and prosperous can also is used by various element of peope as an example of a model in implementing community empowerment.